2018
DOI: 10.1159/000485469
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Evaluating the Physiological Parameters of Performance-Induced Stress in Undergraduate Music Students

Abstract: Music performance anxiety (MPA) is a specific condition for musicians. Although it can have a negative influence on their music careers, little attention is paid to this phenomenon both in the professional environment and in stress research. In the current pilot study, insight was gained into the physiology of the autonomic stress response related to anxiety in musicians when performing on stage by using a wearable biosensor patch for registration of a range of physiological parameters. Also, the validity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This could be explained by the low power of our analysis, but also by the fact that the Kenny Music Performance Anxiety Inventory was not validated for opera singers (Chang-Arana et al, 2018). The lack of significant correlations between the other measures of HRV and music performance anxiety is consistent with previous research reporting no such associations (van Fenema et al, 2017). This calls into question whether the Kenny Music Performance Anxiety Inventory captures how instrumentalists and singers deal with stress onstage.…”
Section: Discussionsupporting
confidence: 91%
“…This could be explained by the low power of our analysis, but also by the fact that the Kenny Music Performance Anxiety Inventory was not validated for opera singers (Chang-Arana et al, 2018). The lack of significant correlations between the other measures of HRV and music performance anxiety is consistent with previous research reporting no such associations (van Fenema et al, 2017). This calls into question whether the Kenny Music Performance Anxiety Inventory captures how instrumentalists and singers deal with stress onstage.…”
Section: Discussionsupporting
confidence: 91%
“…Khalsa and Cope, 2006 ; Khalsa et al, 2009 ; Stern et al, 2012 ; Wells et al, 2012 ; Bissonnette et al, 2015 ; Spahn et al, 2016 ; Juncos et al, 2017 ) and psychometric testing (e.g., Steptoe and Fidler, 1987 ; Kenny et al, 2014 ; Medeiros Barbar et al, 2014 ; Nielsen et al, 2018 ). Physiological measurements of MPA (e.g., Abel and Larkin, 1990 ; Brotons, 1994 ; Yoshie et al, 2009 ; Wells et al, 2012 ; Kenny et al, 2013 ; Studer et al, 2014 ; van Fenema et al, 2017 ; Gomez et al, 2018 ) have also been used as indicators of physiological arousal resulting from activation of the sympathetic division of the Autonomic Nervous System (ANS), for example heart rate, skin conductance, blood pressure, hormone levels, muscle tension and respiration ( Studer et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants were randomly assigned to two seating conditions: visible BIOPAC machine condition (able to observe their physiological outputs in real time throughout the study) or nonvisible BIOPAC condition (machine was out of view of the participant for the entire study) (see Figures 1A and 1B 2 Past research has found no significant physiological arousal or response elicited during completion of baseline questionnaires (van Fenema, Gal, van de Griend, Jacobs, & Cohen, 2017). As result, pretest questionnaires were completed during the baseline phase of the physiological data recording.…”
Section: Methodsmentioning
confidence: 99%
“…2Past research has found no significant physiological arousal or response elicited during completion of baseline questionnaires (van Fenema, Gal, van de Griend, Jacobs, & Cohen, 2017). As result, pretest questionnaires were completed during the baseline phase of the physiological data recording.…”
mentioning
confidence: 99%